2002
DOI: 10.1163/156856202320401979
|View full text |Cite
|
Sign up to set email alerts
|

Improved blood compatibility and decreased VSMC proliferation of surface-modified metal grafted with sulfonated PEG or heparin

Abstract: Although the technique of coronary stenting has remarkably improved long-term results in recent years, (sub)acute thrombosis and late restenosis still remain problems to be solved. Metallic surfaces were regarded as thrombogenic, due to their positive surface charges, and stenosis resulted from the activation and proliferation of vascular smooth muscle cells (VSMCs). In this study, a unique surface modification method for metallic surfaces was studied using a self-assembled monolayer (SAM) technique. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…In addition, it had been confirmed that heparin could inhibit the proliferation of vascular smooth muscle cells (VSMCs) [8]. In the research by Lee [9], heparin was covalently bonded to stainless steel, and an effective inhabitation of VSMCs adhesion and improvement of blood compatibility were achieved. However, the immobilization methods mentioned above are toxic solvent containing, time consuming and relatively complicating with low grafted dense heparin.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, it had been confirmed that heparin could inhibit the proliferation of vascular smooth muscle cells (VSMCs) [8]. In the research by Lee [9], heparin was covalently bonded to stainless steel, and an effective inhabitation of VSMCs adhesion and improvement of blood compatibility were achieved. However, the immobilization methods mentioned above are toxic solvent containing, time consuming and relatively complicating with low grafted dense heparin.…”
Section: Introductionmentioning
confidence: 98%
“…Immobilization of polyethylene glycol (PEG) is the most common approach used to render surfaces resistant to protein adsorption and subsequent cell and platelet adhesion [13][14][15]. However, PEG-modified surfaces are capable of only indirectly and passively inhibiting platelet adhesion and aggregation [16], and PEG indiscriminately blocks cell adhesion, thereby also inhibiting graft endothelialization.…”
Section: Introductionmentioning
confidence: 99%
“…XPS has been used to characterize surfaces of several drug-polymer stent coatings including confirmation of drug identity and the determination of possible chemical reactions with the matrix components. 5,6,[15][16][17] Dynamic time-of-flight mass spectrometry performs destructive depth profiles through drug-polymer coatings for chemically specific information. 13,[18][19][20][21][22] Spectroscopic methods such as near infrared (NIR), Fourier transform infrared (FTIR), and Raman spectroscopy are nondestructive approaches that provide the chemical specificity needed to distinguish an active pharmaceutical ingredient (API) from the matrix components.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the methods with microscopy has provided the ability to map the distribution of polymer blends, pharmaceutical formulations, and drug-polymer coatings on stents. 11,[15][16][17][23][24][25][26][27][28][29][30] Although NIR and FTIR imaging provide chemical selectivity, both suffer from poor spatial resolution and cannot depth profile through coatings. Fluorescence microscopy requires chemical labeling of the drug or a fluorophore inherent to the system.…”
Section: Introductionmentioning
confidence: 99%